BS EN 3-8. Portable fire extinguishers. Part 8. Requirements for the construction, pressure resistance and mechanical tests for extinguishers with a maximum allowable pressure equal to or lower than 30 bar, which comply with the requirements of EN 3-7 (18th May 2020) - British Standards Institution,
No abstract available